Photo-crosslinking organic piezoelectric heterojunction hydrogel as well as preparation method and application thereof
By photocrosslinking organic piezoelectric heterohydrogen gel, combining double-bonded proteins and skeleton materials, the problem of existing piezoelectric materials lacking biologically active signals and functional materials in tissue regeneration is solved, efficient cell differentiation and tissue reconstruction is achieved, and stable electrophysiological signals and mechanical properties are provided.
Patent Information
- Application Number
- CN202411882625.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-19
AI Technical Summary
Existing piezoelectric materials lack effective biological activity signals when promoting muscle and nerve tissue regeneration, and cannot accurately guide cell differentiation and tissue reconstruction. The uneven dispersion of functional materials and unstable binding to hydrogel matrix lead to performance degradation and affecting the repair effect.
提供一种光交联有机压电异质结水凝胶,通过结合双键化蛋白、光引发剂和骨架材料,形成具有良好压电-导电特性和力学性能的水凝胶。 该水凝胶通过共价交联技术将有机压电异质结与凝胶基质紧密结合,确保功能性材料的均匀分散和稳定结合。
It achieves the provision of precise electrophysiological signals, improves compatibility with biological tissues, provides the mechanical stability, piezoelectric properties and the sustained effectiveness of electrical stimulation signals required for muscle contraction and nerve activity, and is suitable for a variety of tissue repair needs.
Smart Images

Figure CN119708866A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of biomedical materials, and in particular relates to a photo-crosslinked organic piezoelectric heterojunction hydrogel and a preparation method and application thereof. Background Art
[0002] Hydrogels play an important role in the biomedical field due to their unique three-dimensional network structure and high water content, especially in tissue engineering, drug delivery systems, cell culture matrices, and biosensors. Since the last century, hydrogels have been widely used in a variety of biomedical applications due to their biocompatibility, plasticity, and structural adjustability. However, traditional hydrogel materials often exhibit insufficient mechanical properties in application scenarios that are subjected to high mechanical loads, such as bone and cartilage repair.
[0003] On the other hand, barium titanate (BaTiO 3 Piezoelectric materials such as polyvinylidene fluoride (PVDF) and polyurethane (PU) can generate electric charge under mechanical stress, and vice versa, that is, they can produce mechanical deformation under the action of electric field. This property makes piezoelectric materials widely used in sensors, actuators and energy harvesting devices. In tissue engineering, piezoelectric materials promote cell proliferation, differentiation and tissue reconstruction by providing additional electrical stimulation signals. Especially in bone and cartilage repair, the electrical stimulation generated by the piezoelectric effect is believed to be able to effectively promote bone cell maturation and mineralization, accelerate cartilage cell growth and tissue repair. At the same time, the conductivity of the material is equally important, especially for muscle and nerve tissue that require electrophysiological signal support. Conductive materials can simulate the electrical properties of natural tissues and provide cells with the necessary electrophysiological environment. In muscle tissue engineering, conductive materials help cells to align and restore their contractile function, and promote muscle cell proliferation and differentiation through continuous electrical stimulation. For neural tissue, conductive materials can act as a good medium for signal transmission, guide axon growth, promote neural network reconstruction, and accelerate neural tissue regeneration.
[0004] Considering the advantages of hydrogels and piezoelectric materials, combining the two to form piezoelectric hydrogels has become an attractive research direction. This type of hydrogel not only inherits the biocompatibility and plasticity of traditional hydrogels, but also incorporates the electrical activity of piezoelectric materials, which can withstand and convert mechanical energy into electrical energy, providing a new solution for tissue repair under mechanical loads.
[0005] However, existing piezoelectric materials often lack effective bioactive signals when promoting muscle and nerve tissue regeneration, and cannot accurately guide cell differentiation and tissue reconstruction. In particular, in nerve regeneration, there is a lack of accurate electrophysiological signals to promote axon growth and neural network reconstruction. At the same time, in existing piezoelectric conductive hydrogels and heterogeneous materials, functional materials such as piezoelectric components are unevenly dispersed and unstable in combination with the hydrogel matrix, which may lead to performance degradation during in vivo application and affect the repair effect. At the same time, traditional hydrogel materials mostly show insufficient mechanical strength when dealing with the mechanical challenges brought by muscle contraction and nerve activity, and it is difficult to meet the stability required for muscle and nerve tissue repair. Summary of the invention
[0006] In view of the above-mentioned deficiencies in the prior art, the present invention provides a photo-crosslinked organic piezoelectric heterojunction hydrogel and a preparation method and application thereof. The photo-crosslinked organic piezoelectric heterojunction hydrogel has good piezoelectric-conductive properties, and the obtained electrical signal is strong and stable. At the same time, it has good mechanical properties itself and has broad application prospects.
[0007] The technical solution adopted to solve the technical problem is to provide a photo-crosslinked organic piezoelectric heterojunction hydrogel, comprising the following raw materials in parts by weight: 5 to 20 parts of double-bonded protein, 0.2 to 0.3 parts of photoinitiator and 0.5 to 4 parts of skeleton material;
[0008] The double-bonded protein is double-bonded gelatin or double-bonded silk protein; the skeleton material is at least one of a composite material of a double-bonded cobalt porphyrin covalent organic skeleton and a hafnium-based metal organic skeleton, a composite material of double-bonded hyaluronic acid and a hafnium-based metal organic skeleton-polypyrrole grafted, and double-bonded silk protein-polypyrrole.
[0009] Preferably, the photo-crosslinked organic piezoelectric heterojunction hydrogel comprises the following raw materials in parts by weight: 10 to 18 parts of double-bonded protein, 0.25 parts of photoinitiator and 1 part of skeleton material.
[0010] Preferably, the photo-crosslinked organic piezoelectric heterojunction hydrogel further comprises 100 parts by weight of water.
[0011] Preferably, the photoinitiator is a LAP photoinitiator.
[0012] Preferably, the double-bonded gelatin is prepared by the following steps:
[0013] Gelatin is dissolved in phosphate buffer at 60°C and methacrylic anhydride is added for reaction, followed by dialyzation and freeze-drying to obtain the product; the mass ratio of gelatin to methacrylic anhydride is 5:6; the reaction temperature is 50°C and the time is 3h; the dialysis temperature is 40°C and the time is 7d, and the water is changed 2 to 3 times a day during the dialysis process.
[0014] Preferably, the double-bonded silk fibroin is prepared by the following steps:
[0015] The degummed silk fibroin is added into the LiBr solution and stirred, and then glycidyl methacrylate is added to react, and after the reaction is completed, the silk fibroin is dialyzed, centrifuged, and the supernatant is freeze-dried to obtain the silk fibroin;
[0016] Among them, the molar concentration of LiBr solution is 9.3M; the mass ratio of glycidyl methacrylate to silk fibroin is 1:1-4; the reaction temperature is 60°C and the time is 4h; the dialysis temperature is 4°C and the time is 7d, and the water is changed 2-3 times a day during the dialysis process.
[0017] Preferably, the double-bonded silk fibroin-polypyrrole is prepared by the following steps:
[0018] The double-bonded silk fibroin is dissolved in a buffer solution, pyrrole is added and stirred, an oxidant is added and stirred for reaction, and then dialyzed and freeze-dried in sequence to obtain the product.
[0019] More preferably, the oxidant is ammonium persulfate; the stirring mixing temperature is 45-50°C and the time is 1.5-2.5h; the stirring reaction temperature is 35-45°C and the time is 8-12h; the dialysis time is 2-3d; the solid-liquid ratio of double-bonded silk fibroin, pyrrole and oxidant is 1g:(300-500)μL:(0.05-0.2)g.
[0020] More preferably, the solid-liquid ratio of double-bonded silk fibroin, pyrrole and oxidant is 1 g:400 μL:0.1 g.
[0021] More preferably, the size of the hafnium-based metal-organic framework is 50 nm.
[0022] More preferably, the hafnium-based metal organic framework is prepared by the following steps:
[0023] (1) HfCl 4 and 2-aminoterephthalic acid are dissolved in N,N-dimethylformamide, water is added for ultrasonication, and then heated for reaction to obtain a suspension;
[0024] (2) The suspension is centrifuged to obtain a precipitate, which is then immersed in N,N-dimethylformamide, taken out, washed, dried, and heated in an inert gas atmosphere to obtain the product.
[0025] More preferably, HfCl 4 The molar ratio of 2-aminoterephthalic acid is 1:2; the heating reaction temperature is 120°C and the time is 24h; the heating treatment temperature is 100°C and the time is 48h.
[0026] Preferably, the composite material of the double-bonded cobalt porphyrin covalent organic framework and the hafnium-based metal organic framework is prepared by the following steps:
[0027] (1) adding cobalt porphyrin, hafnium-based metal organic framework and p-phenylenediamine to polyphosphoric acid in sequence, activating the precursor under sealed conditions after a freeze-thaw cycle, and then heating the reaction to obtain a reactant;
[0028] (2) adjusting the pH of the reactants to 8-9, and then centrifuging, extracting, washing and drying in sequence to obtain composite material particles of cobalt porphyrin covalent organic framework and hafnium-based metal organic framework;
[0029] (3) The composite material particles of the cobalt porphyrin covalent organic framework and the hafnium-based metal organic framework are dispersed in a solvent, ultrasonically treated, and glycidyl methacrylate is added for heating reaction, and then centrifuged, washed, and vacuum dried in sequence to obtain the composite material particles.
[0030] More preferably, in step (1), the precursor activation temperature is 60-70°C, and the time is 10-14h; the heating reaction temperature is 140-160°C, and the time is 55-65h; the solid-liquid ratio of cobalt porphyrin, hafnium-based metal organic framework, p-phenylenediamine and polyphosphoric acid is (20-25) mg: (10-20) mg: (6-9) mg: (2-4) mL.
[0031] More preferably, in step (1), the precursor activation temperature is 66°C and the time is 12h; the heating reaction temperature is 150°C and the time is 60h; the solid-liquid ratio of cobalt porphyrin, hafnium-based metal organic framework, p-phenylenediamine and polyphosphoric acid is 23.7mg:15mg:7.5mg:3mL.
[0032] More preferably, the pH in step (2) is adjusted using a saturated sodium bicarbonate solution; the extraction comprises the following steps: Soxhlet extraction with water, tetrahydrofuran and methanol in sequence; washing time is 24 hours; drying temperature is 90° C., and time is 12 hours.
[0033] More preferably, the solvent in step (3) is tetrahydrofuran; the material-liquid ratio of the composite material of cobalt porphyrin covalent organic framework and hafnium-based metal organic framework to glycidyl methacrylate is (50-70) mg:(200-230) μL; the heating reaction is carried out under stirring conditions at a temperature of 50-60° C. for 34-38 h.
[0034] More preferably, the material-liquid ratio of the composite material of cobalt porphyrin covalent organic framework and hafnium-based metal organic framework to glycidyl methacrylate is 60 mg:215 μL; the heating reaction is carried out under stirring conditions at a temperature of 55° C. for 36 hours.
[0035] More preferably, in step (3), washing is performed with tetrahydrofuran for 3 times, and then washing is performed with chloroform for 3 times under ultrasonic conditions; the vacuum drying temperature is 50° C. and the time is 24 h.
[0036] Preferably, the composite material of double-bonded hyaluronic acid and hafnium-based metal organic framework-polypyrrole grafted is prepared by the following steps:
[0037] (1) dissolving carbodiimide and N-hydroxysuccinimide in water respectively and adding hyaluronic acid aqueous solution to stir and activate, then adding hafnium-based metal organic framework aqueous solution, adjusting the pH to 8-9 and stirring to react, and after the reaction, centrifuging, washing and freeze-drying are performed in sequence to obtain hyaluronic acid-grafted hafnium-based metal organic framework;
[0038] (2) dispersing the hafnium-based metal organic framework grafted with hyaluronic acid in a buffer solution, adding a solvent and methacrylic anhydride to react, then adding anhydrous ethanol to precipitate, wash, dialyze and freeze-dry to obtain a double-bonded hyaluronic acid grafted hafnium-based metal organic framework;
[0039] (3) The hafnium-based metal organic framework grafted with double-bonded hyaluronic acid and pyrrole were dispersed in a hydrochloric acid solution, and then a solution containing FeCl was added. 3 The product is prepared by stirring the mixture with a hydrochloric acid solution and then dialyzing, centrifuging and freeze-drying.
[0040] More preferably, in step (1), the stirring activation temperature is room temperature and the time is 22 to 26 hours; the stirring reaction temperature is 35 to 39° C. and the time is 22 to 26 hours; the mass ratio of carbodiimide, N-hydroxysuccinimide, hyaluronic acid and hafnium-based metal organic framework is (50 to 55):(95 to 99):(25 to 35):(25 to 35); in step (2), the mass ratio of methacrylic anhydride to the hafnium-based metal organic framework grafted with hyaluronic acid is 1 ~2:1~2; the solvent is N,N-dimethylformamide; the reaction temperature is 2~4°C, the time is 22~26h; the dialysis temperature is 35~45°C, and the time is 2~4d; in step (3), the material-liquid ratio of the double-bonded hyaluronic acid-grafted hafnium-based metal organic framework, pyrrole and hydrochloric acid solution is (80~100)mg:(0.03~0.04)mL:(30~60)mL; the molar concentration of the hydrochloric acid solution is 0.05~1M; it contains FeCl 3 FeCl in hydrochloric acid solution 3 The solid-liquid ratio with hydrochloric acid is (0.1-0.3) g:30 mL; the stirring reaction time is 2-6 h.
[0041] More preferably, in step (1), the stirring activation temperature is room temperature and the time is 24 hours; the stirring reaction temperature is 38° C. and the time is 24 hours; and the mass ratio of carbodiimide, N-hydroxysuccinimide, hyaluronic acid and hafnium-based metal organic framework is 52.8:97.8:30:30.
[0042] More preferably, the buffer solution in step (2) is a mixed solution of sodium carbonate and sodium bicarbonate with a pH of 9; the mass ratio of methacrylic anhydride to the hafnium-based metal organic framework grafted with hyaluronic acid is 1:1; the reaction temperature is 4°C and the time is 24h; the dialysis temperature is 40°C and the time is 3d.
[0043] More preferably, in step (3), the material-liquid ratio of the double-bonded hyaluronic acid-grafted hafnium-based metal organic framework, pyrrole and hydrochloric acid solution is 100 mg: 0.037 mL: 30 mL; the molar concentration of the hydrochloric acid solution is 0.1 M; and the FeCl 3 FeCl in hydrochloric acid solution 3 The solid-liquid ratio with hydrochloric acid is 0.2g:30mL; the stirring reaction time is 4h.
[0044] The present invention also provides a method for preparing the above-mentioned photo-crosslinked organic piezoelectric heterojunction hydrogel, comprising the following steps:
[0045] The double-bonded protein, photoinitiator and skeleton material are dissolved in water at 35-38°C, and then irradiated under ultraviolet light for 10-60s to obtain a photo-crosslinked organic piezoelectric heterojunction hydrogel.
[0046] Preferably, the wavelength of ultraviolet light is 360-480 nm, and the light irradiance is 1-10 mW / cm 2 .
[0047] The present invention also provides application of the above-mentioned photo-crosslinked organic piezoelectric heterojunction hydrogel in the preparation of biological tissue engineering repair materials.
[0048] The present invention has the following beneficial effects:
[0049] (1) The photo-crosslinked organic piezoelectric heterojunction hydrogel of the present invention can provide accurate electrophysiological signals through the combination of metal organic framework and conductive material; the metal organic framework and the conductive material not only participate in the formation of piezoelectric heterojunction, but their own conductivity can also increase the overall conductivity of the hydrogel, so that the hydrogel prepared by the present invention can better simulate the conductive properties of natural tissues, and further improve the compatibility with biological tissues;
[0050] (2) In the preparation method of the present invention, the organic piezoelectric heterojunction is tightly combined with the gel matrix through covalent cross-linking technology to form a more solid network structure with better mechanical properties; at the same time, the organic piezoelectric heterojunction in the present invention is evenly distributed in the gel matrix, avoiding the problem of uneven dispersion and easy loss of functional materials in the prior art; when used as a biological tissue engineering repair material, it can provide the mechanical stability, piezoelectric properties and continuous effectiveness of electrical stimulation signals required for muscle contraction and neural activity;
[0051] (3) The photo-crosslinked organic piezoelectric heterojunction hydrogel of the present invention can be customized according to different tissue repair needs, such as muscle repair, nerve repair, bone repair, cartilage regeneration, skin repair, etc., promoting personalized treatment plans for tissue engineering and regenerative medicine, and has wide adaptability;
[0052] (4) The silk fibroin or gelatin matrix selected in the present invention has good biocompatibility, ensuring that the implanted material will not cause immune rejection reaction; at the same time, the degradability of the photo-crosslinked organic piezoelectric heterojunction hydrogel allows it to be gradually absorbed by the body after tissue repair is completed, which is more convenient to use. BRIEF DESCRIPTION OF THE DRAWINGS
[0053] Figure 1 This is the H NMR spectrum of double-bonded silk fibroin;
[0054] Figure 2 is the H NMR spectrum of double-bonded gelatin;
[0055] Figure 3 This is a graph showing the electrochemical test results of the hafnium-based metal-organic framework;
[0056] Figure 4 The figure is the electrochemical test result of the composite material of the double-bonded cobalt porphyrin covalent organic framework and the hafnium-based metal organic framework;
[0057] Figure 5 are hydrogel gelling performance diagrams; wherein, (a) is a gelling performance diagram of 5 parts by weight of double-bonded gelatin; (b) is a gelling performance diagram of 10 parts by weight of double-bonded gelatin; (c) is a gelling performance diagram of 15 parts by weight of double-bonded gelatin; (d) is a gelling performance diagram of the photo-crosslinked organic piezoelectric heterojunction hydrogel prepared in Example 2;
[0058] Figure 6 Graphs showing the gelling properties of hydrogels; wherein (a) is a graph showing the gelling properties of 15 parts by weight of double-bonded silk fibroin; (b) is a graph showing the gelling properties of the photo-crosslinked organic piezoelectric heterojunction hydrogel prepared in Example 4; (c) is a graph showing the gelling properties of the photo-crosslinked organic piezoelectric heterojunction hydrogel prepared in Example 3;
[0059] Figure 7 This is a graph showing the piezoelectric output test results of the photo-crosslinked organic piezoelectric heterojunction hydrogel prepared in Example 1;
[0060] Figure 8 This is a graph showing the piezoelectric output test results of the photo-crosslinked organic piezoelectric heterojunction hydrogels prepared in Example 2 and Comparative Example 2;
[0061] Fig. 9 The graphs are the test results of mechanical properties of the double-bonded silk fibroin, photo-crosslinked organic piezoelectric heterojunction hydrogels prepared in Example 3 and Example 4;
[0062] Fig.10 The figure shows the mechanical properties test results of the double-bonded gelatin and the photo-cross-linked organic piezoelectric heterojunction hydrogel prepared in Example 2. DETAILED DESCRIPTION
[0063] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with embodiment.It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention, that is, the embodiments described are only part of the embodiments of the present invention, rather than all embodiments.If the specific conditions are not indicated in the embodiments, they are carried out according to the conditions recommended by the normal conditions or the manufacturers.If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained by commercial purchase.
[0064] Therefore, the following detailed description of the embodiments of the present invention is not intended to limit the scope of the invention claimed for protection, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without making creative work are within the scope of protection of the present invention.
[0065] The features and performance of the present invention are further described in detail below in conjunction with embodiments.
[0066] Example 1
[0067] A photo-crosslinked organic piezoelectric heterojunction hydrogel comprises the following raw materials in parts by weight: 15 parts of double-bonded silk fibroin, 0.25 parts of LAP photoinitiator, and 1 part of a composite material of double-bonded hyaluronic acid and hafnium-based metal organic framework-polypyrrole grafted;
[0068] Wherein, the double-bonded silk fibroin is prepared by the following steps:
[0069] Prepare a 9.3M LiBr solution and add 10wt% degummed silk fibroin thereto, stir at 60°C until the silk fibroin is completely dissolved, then add glycidyl methacrylate in an equal mass ratio to the silk fibroin, stir and react at 60°C for 4h, after the reaction is completed, put it into a 14kDa dialysis bag, dialyze at 4°C for 7d, change the water 3 times a day, centrifuge and take the supernatant after dialysis, and freeze-dry it to obtain the product;
[0070] The composite material of double-bonded hyaluronic acid and hafnium-based metal organic framework-polypyrrole grafted is prepared by the following steps:
[0071] (1) 0.3 mmol of HfCl 4and 0.6 mmol of 2-aminoterephthalic acid were dissolved in 15 mL of N,N-dimethylformamide, deionized water was added for ultrasonic treatment until the solution was clarified, and then heated at 120°C for 24 hours to obtain a suspension; the suspension was centrifuged to obtain a precipitate and immersed in N,N-dimethylformamide for 72 hours, and the N,N-dimethylformamide was replaced once a day during the immersion process. After being taken out, it was washed with methanol and dried under flowing nitrogen, and then loaded into a gas adsorption tube, and heated at 100°C for 48 hours under a flowing nitrogen atmosphere to obtain a hafnium-based metal organic framework;
[0072] (2) Ultrasonic dispersion of 30 mg of hafnium-based metal organic framework in 10 mL of deionized water to obtain a hafnium-based metal organic framework aqueous solution; dissolving 30 mg of hyaluronic acid in 10 mL of deionized water to obtain a hyaluronic acid aqueous solution; taking another container, dissolving 52.8 mg of carbodiimide and 97.8 mg of N-hydroxysuccinimide in 1.5 mL of deionized water respectively and adding the hyaluronic acid aqueous solution to the solution, stirring and activating at room temperature for 24 h, then adding the hafnium-based metal organic framework aqueous solution, adjusting the pH to 9 with triethanolamine and stirring the solution at 38° C. for 24 h, and after the reaction, centrifuging at 21000 rpm in sequence, taking the precipitate and washing it with deionized water for 3 times, and then freeze-drying it to obtain a hafnium-based metal organic framework grafted with hyaluronic acid;
[0073] (3) preparing a mixed solution of sodium carbonate and sodium bicarbonate with a pH of 9 as a buffer solution, dispersing the hafnium-based metal organic framework grafted with hyaluronic acid in 50 mL of the buffer solution and stirring for 30 min, then adding 25 mL of N,N-dimethylformamide and methacrylic anhydride in an equal mass ratio to the hafnium-based metal organic framework grafted with hyaluronic acid under ice bath conditions at 4°C for reaction for 24 h, then adding 5 times the volume of anhydrous ethanol for precipitation and washing, dialyzing at 40°C for 3 days and freeze-drying to obtain a double-bonded hyaluronic acid grafted hafnium-based metal organic framework;
[0074] (4) 100 mg of the double-bonded hyaluronic acid-grafted hafnium-based metal organic framework and 37 μL of pyrrole were dispersed in 30 mL of 0.1 M hydrochloric acid solution and subjected to ultrasonic treatment for 30 min. Then, 0.2 g of FeCl was added dropwise in an ice bath at 4 °C. 3 30 mL of 0.1 M hydrochloric acid solution was added and stirred for 4 h, followed by 3 d of dialysis, centrifugation and freeze-drying to obtain the product.
[0075] The H NMR spectrum of double bonded silk fibroin (SilMA) is shown in Figure 1 As shown, from Figure 1 It can be seen that the double-bonded silk fibroin was successfully synthesized.
[0076] This embodiment also provides a method for preparing the above-mentioned photo-crosslinked organic piezoelectric heterojunction hydrogel, comprising the following steps:
[0077] The double-bonded silk fibroin, LAP photoinitiator, double-bonded hyaluronic acid and hafnium-based metal organic framework-polypyrrole grafted composite material were dissolved in 100 parts by weight of water at 37°C, and then irradiated with light at a wavelength of 360-480nm and an irradiance of 1-10mW / cm 2 The photo-crosslinked organic piezoelectric heterojunction hydrogel was obtained by irradiating the sample under ultraviolet light for 60 seconds.
[0078] Example 2
[0079] A photo-crosslinked organic piezoelectric heterojunction hydrogel comprises the following raw materials in parts by weight: 10 parts of double-bonded gelatin, 0.25 parts of LAP photoinitiator, and 1 part of a composite material of a double-bonded cobalt porphyrin covalent organic framework and a hafnium-based metal organic framework;
[0080] Wherein, the double-bonded gelatin is prepared by the following steps:
[0081] Dissolve 20g gelatin in 200mL phosphate buffer at 60℃ and add 24g methacrylic anhydride to react at 50℃ for 3h, then dialyze at 40℃ for 7d, change water twice a day during the dialysis process, and then freeze-dry to obtain the product;
[0082] The composite material of the double-bonded cobalt porphyrin covalent organic framework and the hafnium-based metal organic framework is prepared by the following steps:
[0083] (1) 0.3 mmol of HfCl 4 and 0.6 mmol of 2-aminoterephthalic acid were dissolved in 15 mL of N,N-dimethylformamide, deionized water was added for ultrasonic treatment until the solution was clarified, and then heated at 120°C for 24 hours to obtain a suspension; the suspension was centrifuged to obtain a precipitate and immersed in N,N-dimethylformamide for 72 hours, and the N,N-dimethylformamide was replaced once a day during the immersion process. After being taken out, it was washed with methanol and dried under flowing nitrogen, and then loaded into a gas adsorption tube, and heated at 100°C for 48 hours under a flowing nitrogen atmosphere to obtain a hafnium-based metal organic framework;
[0084] (2) 23.7 mg of cobalt porphyrin, 15 mg of hafnium-based metal organic framework and 7.5 mg of p-phenylenediamine were added to a 10 mL Pyrex glass tube, and then added to 3 mL of polyphosphoric acid. After three cycles of freeze pump-thaw, the N 2 The protective tube was sealed and the precursor was activated at 66°C for 12 hours, and then heated at 150°C for 60 hours. After the reaction was completed, it was naturally cooled to room temperature and then transferred to a beaker to obtain the reactant;
[0085] (3) adjusting the pH of the reactants to 8-9 with a saturated sodium bicarbonate solution, centrifuging to obtain a precipitate, performing Soxhlet extraction with water, tetrahydrofuran and methanol, respectively, and washing for 24 hours, and drying at 90° C. for 12 hours to obtain composite material particles of cobalt porphyrin covalent organic framework and hafnium-based metal organic framework;
[0086] (4) 60 mg of the composite material particles of cobalt porphyrin covalent organic framework and hafnium-based metal organic framework were dispersed in 5 mL of tetrahydrofuran and ultrasonicated for 20 min, and 215 μL of glycidyl methacrylate was added and stirred at 55° C. for heating reaction for 36 h, and then centrifuged, washed with tetrahydrofuran for 3 times, and then washed with chloroform under ultrasonic conditions for 3 times, and then vacuum dried at 50° C. for 24 h.
[0087] The H NMR spectrum of double bonded gelatin (GelMA) is as follows Figure 2 As shown, from Figure 2 It can be seen that the double-bonded gelatin was successfully synthesized.
[0088] This embodiment also provides a method for preparing the above-mentioned photo-crosslinked organic piezoelectric heterojunction hydrogel, comprising the following steps:
[0089] The composite material of double-bonded gelatin, LAP photoinitiator, double-bonded cobalt porphyrin covalent organic framework and hafnium-based metal organic framework is dissolved in 100 parts by weight of water at 37°C, and then irradiated with light at a wavelength of 360-480nm and an irradiance of 1-10mW / cm 2 The photo-crosslinked organic piezoelectric heterojunction hydrogel was obtained by irradiating the sample under ultraviolet light for 60 seconds.
[0090] Example 3
[0091] A photo-crosslinked organic piezoelectric heterojunction hydrogel comprises the following raw materials in parts by weight: 15 parts of double-bonded silk fibroin, 3 parts of double-bonded silk fibroin-polypyrrole, 0.25 parts of LAP photoinitiator, and 1 part of a composite material of double-bonded hyaluronic acid and hafnium-based metal organic framework-polypyrrole grafted;
[0092] The preparation of the composite material of double-bonded silk fibroin, double-bonded hyaluronic acid and hafnium-based metal organic framework-polypyrrole grafted is the same as in Example 1;
[0093] Wherein, the double-bonded silk fibroin-polypyrrole is prepared by the following steps:
[0094] (1) preparing a 9.3M LiBr solution and adding 10 wt% degummed silk fibroin thereto, stirring at 60°C until the silk fibroin is completely dissolved, then adding glycidyl methacrylate in an equal mass ratio to the silk fibroin, stirring and reacting at 60°C for 4 hours, and after the reaction is completed, placing it in a 14 kDa dialysis bag, dialyzing it at 4°C for 7 days, changing the water 3 times a day, and after the dialysis is completed, centrifuging and taking the supernatant for freeze-drying to obtain double-bonded silk fibroin;
[0095] (2) 1 g of double-bonded silk fibroin was dissolved in phosphate buffer at 45°C and 400 μL of pyrrole was added and mixed by magnetic stirring for 2 h. Then 0.1 g of ammonium persulfate was added and stirred at 40°C for 12 h. The mixture was dialyzed for 3 days and freeze-dried to obtain the obtained product.
[0096] This embodiment also provides a method for preparing the above-mentioned photo-crosslinked organic piezoelectric heterojunction hydrogel, comprising the following steps:
[0097] The double-bonded silk fibroin, double-bonded silk fibroin-polypyrrole, LAP photoinitiator, double-bonded hyaluronic acid and hafnium-based metal organic framework-polypyrrole grafted composite material were dissolved in 100 parts by weight of water at 37°C, and then irradiated with light at a wavelength of 360-480nm and an irradiance of 1-10mW / cm 2 The photo-crosslinked organic piezoelectric heterojunction hydrogel was obtained by irradiating the sample under ultraviolet light for 60 seconds.
[0098] Example 4
[0099] A photo-crosslinked organic piezoelectric heterojunction hydrogel comprises the following raw materials in parts by weight: 15 parts of double-bonded silk fibroin, 0.25 parts of LAP photoinitiator and 3 parts of double-bonded silk fibroin-polypyrrole;
[0100] The preparation of double-bonded silk fibroin is the same as in Example 1; the preparation of double-bonded silk fibroin-polypyrrole is the same as in Example 3.
[0101] This embodiment also provides a method for preparing the above-mentioned photo-crosslinked organic piezoelectric heterojunction hydrogel, comprising the following steps:
[0102] The double-bonded silk fibroin, double-bonded silk fibroin-polypyrrole and LAP photoinitiator were dissolved in 100 parts by weight of water at 37°C, and then irradiated with light at a wavelength of 360-480nm and an irradiance of 1-10mW / cm 2 The photo-crosslinked organic piezoelectric heterojunction hydrogel was obtained by irradiating the sample under ultraviolet light for 60 seconds.
[0103] Comparative Example 1
[0104] A photo-crosslinked organic piezoelectric heterojunction hydrogel comprises the following raw materials in parts by weight: 15 parts of double-bonded silk fibroin, 0.25 parts of LAP photoinitiator and 1 part of hafnium-based metal organic framework;
[0105] Wherein, the preparation of double-bonded silk fibroin is the same as in Example 1;
[0106] Wherein, the hafnium-based metal organic framework is prepared by the following steps:
[0107] 0.3 mmol HfCl 4 and 0.6 mmol of 2-aminoterephthalic acid are dissolved in 15 mL of N,N-dimethylformamide, deionized water is added for ultrasonic treatment until the solution is clarified, and then heated at 120°C for 24 hours to obtain a suspension; the suspension is centrifuged to obtain a precipitate and immersed in N,N-dimethylformamide for 72 hours, and the N,N-dimethylformamide is replaced once a day during the immersion process. After taking out, it is washed with methanol and dried under flowing nitrogen, and then loaded into a gas adsorption tube and heated at 100°C for 48 hours under a flowing nitrogen atmosphere to obtain.
[0108] This comparative example also provides a method for preparing the above-mentioned photo-crosslinked organic piezoelectric heterojunction hydrogel, comprising the following steps:
[0109] The double-bonded silk fibroin, LAP photoinitiator and hafnium-based metal organic framework were dissolved in 100 parts by weight of water at 37°C, and then irradiated with light at a wavelength of 360-480nm and an irradiance of 1-10mW / cm 2 The photo-crosslinked organic piezoelectric heterojunction hydrogel was obtained by irradiating the sample under ultraviolet light for 60 seconds.
[0110] Comparative Example 2
[0111] A photo-crosslinked organic piezoelectric heterojunction hydrogel comprises the following raw materials in parts by weight: 10 parts of double-bonded gelatin, 0.25 parts of LAP photoinitiator and 1 part of hafnium-based metal organic framework;
[0112] The preparation of double-bonded silk fibroin is the same as that in Example 2; and the preparation of hafnium-based metal organic framework is the same as that in Comparative Example 1.
[0113] This comparative example also provides a method for preparing the above-mentioned photo-crosslinked organic piezoelectric heterojunction hydrogel, comprising the following steps:
[0114] Double-bonded gelatin, LAP photoinitiator and hafnium-based metal organic framework were dissolved in 100 parts by weight of water at 37°C, and then irradiated with light at a wavelength of 360-480nm and an irradiance of 1-10mW / cm 2 The photo-crosslinked organic piezoelectric heterojunction hydrogel was obtained by irradiating the sample under ultraviolet light for 60 seconds.
[0115] Experimental example
[0116] 1. The hafnium-based metal organic framework (MOF) obtained in step (1) of preparing the composite material of the double-bonded cobalt porphyrin covalent organic framework and the hafnium-based metal organic framework in Example 2 is divided into three types according to different sizes: MOF-L (400 nm), MOF-M (200 nm) and MOF-S (50 nm). MOF-L, MOF-M, MOF-S and the composite material of the double-bonded cobalt porphyrin covalent organic framework and the hafnium-based metal organic framework (MOF@COF) prepared in Example 2 were subjected to electrochemical tests. The MOF treatment method was as follows: 10 mg of MOF or MOF@COF was dispersed in a mixed solution of 0.5 mL of ethanol and 20 μL of Nafion solution (5%), respectively. After ultrasonic treatment for 30 min, 20 μL of the mixed solution was transferred to a glassy carbon electrode with a diameter of 5 mm and air-dried for 12 h. The specific test method was as follows: the electrochemical impedance spectroscopy was tested on a piezoelectric ceramic using an electrochemical workstation (Versa STAT3F, Ametek, USA). The working electrode was a sample-loading electrode, the auxiliary electrode was a platinum sheet (1-2×1-2 cm), and the reference electrode was a saturated Ag / AgCl electrode. In 0.5 M Na 2 SO 4 Solution and 0.1~10 5 Electrochemical impedance spectroscopy (EIS) was recorded with an alternating current of 5 mV amplitude in the frequency range of 1 Hz; the results are shown in Figures 3-4 shown.
[0117] from Figures 3-4 It can be seen that the smaller MOF-S has a lower impedance value, and the composite material of the double-bonded cobalt porphyrin covalent organic framework synthesized using MOF-S and the hafnium-based metal organic framework has better electrochemical performance.
[0118] 2. The gelling properties of double-bonded gelatin, double-bonded silk fibroin, and the photo-crosslinked organic piezoelectric heterojunction hydrogels prepared in Examples 2 to 4 with different concentrations were studied. Figures 5-6 shown.
[0119] from Figure 5 It can be seen that the gelling performance of 5 weight parts of double-bonded gelatin is poor, and the gelling performance of 10-15 weight parts of double-bonded gelatin is good. The photo-crosslinked organic piezoelectric heterojunction hydrogel prepared with 10 weight parts of double-bonded gelatin as raw material can be well gelled; Figure 6 It can be seen that 15 parts by weight of double-bonded silk fibroin and the photo-crosslinked organic piezoelectric heterojunction hydrogel prepared with 15 parts by weight of double-bonded silk fibroin as raw materials have good gelling properties.
[0120] 3. The MOF-L, MOF-M, MOF-S obtained in 1 and the double-bonded silk fibroin are subjected to the action of LAP photoinitiator to form hydrogels, namely SilMA+MOF-L, SilMA+MOF-M and SilMA+MOF-S (Comparative Example 1); the above hydrogels and the photo-crosslinked organic piezoelectric heterojunction hydrogels prepared in Example 1, and the photo-crosslinked organic piezoelectric heterojunction hydrogels prepared in Example 2 and Comparative Example 2 are subjected to piezoelectric output tests, respectively. The specific method is: using a homemade electromechanical system to apply cyclic compression loads of various frequencies, using a charge amplifier (kd5002, Jiangsu Baofei Vibration Instrument Co., Ltd., China) to measure the charge signal generated by each piezoelectric hydrogel, and converting the charge into a voltage signal output; using a data acquisition card (HK_USB6202-SDIEIE, HKTECH Co., Ltd., Zhengzhou, China) to obtain the signal output by the charge amplifier, and finally using Labview software to record and display in real time on a computer. The results are shown in FIG. Figures 7-8 shown.
[0121] from Figure 7 and Figure 8 It can be seen that the heterojunction formed in the photo-cross-linked organic piezoelectric heterojunction hydrogel prepared by the present invention can effectively increase the piezoelectric output of the hydrogel, has a good piezoelectric signal, and performs well in electrophysiological signal transmission, providing new possibilities for its application in nerve and muscle tissue repair.
[0122] 4. The mechanical properties of the gelled double-bonded silk fibroin (SilMA), the photo-crosslinked organic piezoelectric heterojunction hydrogels prepared in Examples 3 and 4, the gelled double-bonded gelatin (GelMA) and the photo-crosslinked organic piezoelectric heterojunction hydrogel prepared in Example 2 were tested respectively. The specific method is as follows: the rheological behavior was measured on a rotational rheometer (DHR-1, TA Instruments, USA) with a parallel plate configuration (diameter 20 mm, gap 1 mm); first, the linear viscoelastic region (LVR) of the sample was measured by amplitude (strain) scanning, and the oscillation strain was increased from 0.001% to 50% at a constant frequency of 1 Hz; then, under a fixed shear strain within the LVR, the dynamic storage modulus (G′) and loss modulus (G″) were measured in the frequency range of 0.1 to 10 Hz, and each test procedure required the addition of 500 μL of sample to the plate; the results are shown in FIG. Figures 9-10 shown.
[0123] from Figures 9-10 It can be seen that the photo-crosslinked organic piezoelectric heterojunction hydrogel in the present invention tightly combines the organic piezoelectric heterojunction with the gel matrix through covalent crosslinking technology, forming a heterojunction structure formed by a more solid network structure, and the mechanical properties of the hydrogel can be further improved.
[0124] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A photo-crosslinked organic piezoelectric heterojunction hydrogel, characterized in that: The method comprises the following raw materials in parts by weight: 5 to 20 parts of double-bonded protein, 0.2 to 0.3 parts of photoinitiator and 0.5 to 4 parts of skeleton material; The double-bonded protein is double-bonded gelatin or double-bonded silk protein; the skeleton material is at least one of a composite material of a double-bonded cobalt porphyrin covalent organic skeleton and a hafnium-based metal organic skeleton, a composite material of double-bonded hyaluronic acid and a hafnium-based metal organic skeleton-polypyrrole grafted, and double-bonded silk protein-polypyrrole.
2. The photo-crosslinked organic piezoelectric heterojunction hydrogel according to claim 1, characterized in that: The double-bonded silk fibroin-polypyrrole is prepared by the following steps: The double-bonded silk fibroin is dissolved in a buffer solution, pyrrole is added and stirred, an oxidant is added and stirred for reaction, and then dialyzed and freeze-dried in sequence to obtain the product.
3. The photo-crosslinked organic piezoelectric heterojunction hydrogel according to claim 2, characterized in that: The oxidant is ammonium persulfate; the stirring mixing temperature is 45-50°C and the time is 1.5-2.5h; the stirring reaction temperature is 35-45°C and the time is 8-12h; the dialysis time is 2-3d; the solid-liquid ratio of the double-bonded silk fibroin, pyrrole and oxidant is 1g:(300-500)μL:(0.05-0.2)g.
4. The photo-crosslinked organic piezoelectric heterojunction hydrogel according to claim 1, characterized in that: The composite material of the double-bonded cobalt porphyrin covalent organic framework and the hafnium-based metal organic framework is prepared by the following steps: (1) adding cobalt porphyrin, hafnium-based metal organic framework and p-phenylenediamine to polyphosphoric acid in sequence, activating the precursor under sealed conditions after a freeze-thaw cycle, and then heating the reaction to obtain a reactant; (2) adjusting the pH of the reactants to 8-9, and then centrifuging, extracting, washing and drying in sequence to obtain composite material particles of cobalt porphyrin covalent organic framework and hafnium-based metal organic framework; (3) The composite material particles of the cobalt porphyrin covalent organic framework and the hafnium-based metal organic framework are dispersed in a solvent, ultrasonically treated, and glycidyl methacrylate is added for heating reaction, and then centrifuged, washed, and vacuum dried in sequence to obtain the composite material particles.
5. The photo-crosslinked organic piezoelectric heterojunction hydrogel according to claim 4, characterized in that: In the step (1), the precursor activation temperature is 60-70° C. and the time is 10-14 h; the heating reaction temperature is 140-160° C. and the time is 55-65 h; the material-liquid ratio of the cobalt porphyrin, hafnium-based metal organic framework, p-phenylenediamine and polyphosphoric acid is (20-25) mg: (10-20) mg: (6-9) mg: (2-4) mL.
6. The photoelectric heterojunction hydrogel according to claim 4, characterized in that: The solvent in step (3) is tetrahydrofuran; the material-liquid ratio of the composite material of cobalt porphyrin covalent organic framework and hafnium-based metal organic framework to glycidyl methacrylate is (50-70) mg: (200-230) μL; the heating reaction is carried out under stirring conditions at a temperature of 50-60° C. and a time of 34-38 hours.
7. The photo-crosslinked organic piezoelectric heterojunction hydrogel according to claim 1, characterized in that: The double-bonded hyaluronic acid and hafnium-based metal organic framework-polypyrrole grafted composite material is prepared by the following steps: (1) dissolving carbodiimide and N-hydroxysuccinimide in water respectively and adding hyaluronic acid aqueous solution to stir and activate, then adding hafnium-based metal organic framework aqueous solution, adjusting the pH to 8-9 and stirring to react, and after the reaction, centrifuging, washing and freeze-drying are performed in sequence to obtain hyaluronic acid-grafted hafnium-based metal organic framework; (2) dispersing the hafnium-based metal organic framework grafted with hyaluronic acid in a buffer solution, adding a solvent and methacrylic anhydride to react, then adding anhydrous ethanol to precipitate, wash, dialyze and freeze-dry to obtain a double-bonded hyaluronic acid grafted hafnium-based metal organic framework; (3) The hafnium-based metal organic framework grafted with double-bonded hyaluronic acid and pyrrole are dispersed in a hydrochloric acid solution, and then a hydrochloric acid solution containing FeCl3 is dropped into the solution and stirred for reaction, followed by dialysis, centrifugation and freeze-drying to obtain the product.
8. The photo-crosslinked organic piezoelectric heterojunction hydrogel according to claim 7, characterized in that: In the step (1), the stirring activation temperature is room temperature and the time is 22 to 26 hours; the stirring reaction temperature is 35 to 39° C. and the time is 22 to 26 hours; the mass ratio of the carbodiimide, N-hydroxysuccinimide, hyaluronic acid and hafnium-based metal organic framework is (50 to 55):(95 to 99):(25 to 35):(25 to 35); in the step (2), the mass ratio of methacrylic anhydride to the hafnium-based metal organic framework grafted with hyaluronic acid is 1 to 2:1 to 2; the solvent is N,N-dimethylformamide; the reaction temperature is 2-4°C, for 22-26h; the dialysis temperature is 35-45°C, for 2-4d; the solid-liquid ratio of the double-bonded hyaluronic acid grafted hafnium-based metal organic framework, pyrrole and hydrochloric acid solution in step (3) is (80-100)mg:(0.03-0.04)mL:(30-60)mL; the molar concentration of the hydrochloric acid solution is 0.05-1M; the solid-liquid ratio of FeCl3 to hydrochloric acid in the hydrochloric acid solution containing FeCl3 is (0.1-0.3)g:30mL; the stirring reaction time is 2-6h.
9. The method for preparing the photo-crosslinked organic piezoelectric heterojunction hydrogel according to any one of claims 1 to 8, characterized in that: The following steps are involved: The double-bonded protein, photoinitiator and skeleton material are dissolved in water at 35-38°C, and then irradiated under ultraviolet light for 10-60s to obtain a photo-crosslinked organic piezoelectric heterojunction hydrogel.
10. Use of the photo-crosslinked organic piezoelectric heterojunction hydrogel according to any one of claims 1 to 8 in the preparation of biological tissue engineering repair materials.
Citation Information
Patent Citations
Modification method of photocrosslinked silk fibroin and preparation method of in-situ drug-loaded hydrogel of photocrosslinked silk fibroin
CN106977670A
Visible-light responsive hafnium-based metal-organic framework material and preparation method thereof
CN108997591A
Photocuring fibroin / hyaluronic acid hydrogel as well as preparation method and application thereof
CN115260527A
Photosensitive silk fibroin flexible gel and preparation method thereof
CN115466410A
Photo-crosslinked silk fibroin / hyaluronic acid hydrogel barrier material as well as preparation method and application thereof
CN116217943A